(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
Adequate heat balance is critical to human performance in the heat. If heat balance cannot be maintained, the core temperature increases and body water dehydration leads to exhaustion and limit the performance. Clothing heat transfer properties, thermal insulation and water vapour resistance, modify heat exchange and may indirectly affect performance. Work in protective clothing quickly becomes exhaustive in impermeable garments, but can be easily completed with much less strain in permeable garments. Athletes, in particular in sports of endurance type, may produce more than 1000 W/m2 in an event lasting several hours. Physical examination of the heat balance of a runner reveals that a 20% lower water vapour resistance of a covering running suit allows the runner a longer run time or a higher speed per km before critical physiological strain is reached.